Vulnerabilidade de gênero na internet: o machismo no ambiente digital - Bastos, Caroline Ayala de Carvalho (2024)
The present academic study addresses gender violence in the digital space, demonstrating that this environment is currently configured as a new space of gender vulnerability, based on new forms of violence, which mostly victimize women, through behaviors such as the non-consensual dissemination of intimate images and videos, known as revenge pornography, as well as sextortion, stalking, cyberbulling and doxing. Therefore, it seeks to systematize and categorize this universe of violations of women's human rights under the concept of online violence, demonstrating its connection with contemporary expressions of machismo, misogyny and structural patriarchy. The main objective is to demonstrate that digital gender violence is a direct consequence of the structural machismo outlined within the patriarchal society scheme in which we live and that violence in the online environment, considered its intrinsic peculiarities, is, at the same time, a reflection and extension of gender violations already occurring in the physical environment. The digital world seems to increasingly conform a space of vulnerability (FEITO, 2007) for women as well as for other vulnerable groups. The absence of the domain of Law and the naturalization of gender prejudices indicate that in order to make it possible to advance in the adoption of measures to face this scenario of violence that affects women, more than ever it is necessary for us to know, problematize and give critical visibility to these forms of violence. From the survey and analysis of secondary data produced by Safernet, in Brazil, from 2017 to 2022, it appears that in about 70% of cases of digital violence the victims are women. The visibility and knowledge about these contemporary expressions of gender violence associated with the digital world corroborate the need for regulation and control of networks and platforms, as well as the deepening of debates on digital democracy and gender democracy (RE, 2019) Such a panorama requires the legal order to be responsible for changing the focus of constitutional discussion, through the introduction of Feminist Constitutionalism, from a gender perspective, based, including, on a multilevel legal space, which works as an instrument of expansive force for the protection of women's human rights.